Formation of an extended CoSi2 thin nanohexagons array coherently buried in silicon single crystal - Kellermann, Guinther (2012)
A Co-doped silica film was deposited on the surface of a Si(100) wafer and isothermally annealed at 750 °C to form spherical Co nanoparticles embedded in the silica film and a few atomic layer thick CoSi 2 nanoplatelets within the wafer. The structure, morphology, and spatial orientation of the nanoplatelets were characterized. The experimental results indicate that the nanoplatelets exhibit hexagonal shape and a uniform thickness. The CoSi 2 nanostructures lattice is coherent with the Si lattice, and each of them is parallel to one of the four planes belonging to the {111} crystallographic form of the host lattice.